ICT innovations 2010 second international conference, ICT Innovations 2010, Ohrid, Macedonia, September 12-15, 2010. Revised selected papers - Gusev, Marjan; Mitrevsky, Pece (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the Second International Conference, ICT Innovations 2010, held in Ohrid, Macedonia, in September 2010. The 33 revised papers presented together with 5 invited papers were carefully reviewed and selected. The papers address the following topics: internet applications and services, artificial intelligence, bioinformatics, internet, mobile and wireless technologies, multimedia information systems, computer networks, computer security, e-business, cryptography, high-performance-computing, social networks, e-government, as well as GPU computing.